An identical-by-descent segment harbors a 12-bp insertion determining fruit softening during domestication and speciation in Pyrus - Bobo Song; Xiaolong Li; Beibei Cao; Mingyue Zhang; Schuyler S. Korban; Li’ang Yu; Wenxi Yang; Kejiao Zhao; Jiaming Li; Jun Wu (BMC Biology, 2022)
Abstract Background Although the wild relatives of pear originated in southwest China, this fruit crop was independently domesticated and improved in Asia and Europe, and there are major phenotypic differences (e.g., maturity and fruit firmness) between Asian and European pears.  Results In this study, we examined the genomes of 113 diverse pear accessions using an identity-by-descent (IBD) approach to investigate how historical gene flow has shaped fruit firmness traits in Asian and European pears. We found a 3-Mbp IBD-enriched region (IBD-ER) that has undergone “convergent domestication” in both the Asian and European pear lineages, and a genome-wide association study (GWAS) of fruit firmness phenotypes strongly implicated the TRANSLOCON AT THE INNER CHLOROPLAST ENVELOPE55 (TIC55) locus within this 3-Mbp IBD-ER. Furthermore, we identified a tandem duplication that includes a 12-bp insertion located in the first exon of TIC55 that is uniquely present in Asian pears, and expression analysis showed that the pear TIC55 gene is highly expressed in Asian pear, while it is weakly or not expressed in European pear; this could contribute to the differences in fruit firmness between Asian and European pear fruits. Conclusions Our findings provide insights into how pear fruit softening has been impacted during domestication, and we identified candidate genes associated with fruit softening that can contribute to the breeding and improvement of pear and other fruit crops.